2022
DOI: 10.1002/pon.6064
|View full text |Cite
|
Sign up to set email alerts
|

Duration of the patient interval in breast cancer and factors associated with longer delays in low‐and middle‐income countries: A systematic review with meta‐analysis

Abstract: Objective: Breast cancer survival is lower in low-and middle-income countries (LMICs) partially due to many women being diagnosed with late-stage disease. The patient interval refers to the time elapsed between the detection of symptoms and the first consultation with a healthcare provider and is considered one of the core indicators for early diagnosis and treatment. The goal of the current research was to conduct a meta-analysis of the duration of the patient interval in LMICs and investigate the socio-demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…Thaduria et al 16 report on the association between financial toxicity, employment and well-being in oral cancer survivors in a sub-Himalayan city in North India in the era of Covid-19. In a systematic review of the duration of time from symptom onset to the first consultation with a health professional in breast cancer patients, Petrova et al 17 demonstrated the role that literacy and education, stigma, low socioeconomic status and social support play in delaying help-seeking in this population. Ainembabazi et al 18 have demonstrated the link between perception of risk and seeking of screening in female relatives of patients with breast cancer in Uganda.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 99%
“…Thaduria et al 16 report on the association between financial toxicity, employment and well-being in oral cancer survivors in a sub-Himalayan city in North India in the era of Covid-19. In a systematic review of the duration of time from symptom onset to the first consultation with a health professional in breast cancer patients, Petrova et al 17 demonstrated the role that literacy and education, stigma, low socioeconomic status and social support play in delaying help-seeking in this population. Ainembabazi et al 18 have demonstrated the link between perception of risk and seeking of screening in female relatives of patients with breast cancer in Uganda.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 99%